1. Axonal function in inflammatory neuropathy: The importance of conduction block. Issue 4 (April 2018) - Garg, Nidhi; Park, Susanna B.; Howells, James; Noto, Yu-ichi; Yiannikas, Con; Krishnan, Arun V.; Spies, Judith; Pollard, John D.; Vucic, Steve; Bostock, Hugh; Kiernan, Matthew C.
Abstract : Introduction: Conduction block (CB) is a pathognomonic feature of chronic inflammatory demyelinating polyneuropathy (CIDP) and multifocal motor neuropathy (MMN), but precise mechanisms remain elusive. The aim of this study was to determine whether median motor axonal excitability profiles differ in MMN vs CIDP associated with conduction block (CB). Methods: Clinical assessments, nerve conduction studies, median motor axonal excitability studies and ultrasound testing was undertaken in 12 patients with MMN and 44 patients with CIDP with results compared with 29 age-matched healthy controls. Results: Compared to healthy controls, MMN with median motor CB was associated with greater threshold changes in threshold electrotonus (TE) in both depolarising [TEd 90–100 ms: 53.1 ± 1.8% vs 44.7 ± 0.7%; p < 0.0001] and hyperpolarizing directions [TEh 90–100 ms: −147.6 ± 8.1% vs −113.3 ± 3.3%; p < 0.0001] in addition to much greater superexcitability (−39.3 ± 2.0% vs −23.2 ± 1.0%; p < 0.0001). CIDP patients with median motor CB demonstrated similar threshold changes in TE (p < 0.0001) but without superexcitability change. CIDP patients without median motor CB did not differ from healthy controls in TE and superexcitability parameters. Patients with CIDP with and without block had similar median nerve cross-sectional areas. Conclusion: Axonal excitability patterns differ in patients with MMN and CIDP with CB demonstrating differences in underlying pathophysiology. Differences in excitability patterns in patients with CIDP with and without block cannot be explained by structural differences.